Balancing Economic and Environmental Performance for Small-Scale Rice Farmers in Peru - White, Marshal; Heros, Elizabeth; Graterol, Eduardo; Chirinda, Ngonidzashe; Pittelkow, Cameron M. (Frontiers in Sustainable Food Systems, 2020)
Integrated research efforts are needed to provide insights for simultaneously achieving food production and environmental goals in rice production systems. In this study we evaluated eight Sustainable Rice Platform performance indicators (net profit, labor productivity, grain yield, water use efficiency, nitrogen use efficiency, phosphorus use efficiency, pesticide use efficiency, and greenhouse gas emissions) for 65 rice farmers in Peru. The aim was to 1) identify the major management factors influencing profitability, 2) evaluate potential tradeoffs between economic and environmental sustainability, and 3) understand farmer perceptions and decision-making processes related to profitability. For data analysis, farmers were grouped into profitability categories based on net profit: top (top 20%), middle (middle 60%), and bottom (bottom 20%). Our results indicate that rice yields, grain sale price, and total spending drive profitability in this region of Peru. An important finding is that the top profitability group achieved higher yields while using lower inputs of labor, pesticides, elemental P, and irrigation hours, resulting in improved environmental performance (e.g. higher nutrient and water use efficiency and lower greenhouse gas emissions). Results from focus group discussions highlighted that rice production has changed in recent decades, and there is a need for improved extension support to cope with increasing pests, disease, and water scarcity. Moreover, farmers indicated they are vulnerable to exploitation from vendors along the rice supply chain, with limited access to credit facilities and market channels and little negotiating power over the cost of inputs and rice sale price. Overall, our results suggest that rice productivity and profitability can be improved in this region without negatively influencing environmental footprint per unit production, yet this is unlikely to occur unless key agronomic and socioeconomic challenges are addressed, such as improved access to crop management recommendations, alternative financing and credit options, and technologies that decrease the costs of production.